Advances in global leadership - Osland, Joyce; Reiche, B. Sebastian; Szkudlarek, Betina; Mendenhall, Mark E., 1956- (Advances in global leadership ;, 2019)
This volume continues to advance both global leadership research and practice by bridging and integrating conceptual, empirical and practitioner perspectives to provide a deeper understanding of this rapidly growing field of study. Part I brings together conceptual, qualitative, and quantitative work to present innovative foundational research on the concept and processes of global leadership and global competence development. Part II, the Practitioner's Corner, features chapters and interviews with pioneers in the field and the lessons they learned from decades of global leadership development in university, corporate and government settings. The editors conclude with an analysis of the global leadership research published in 2018 and its implications. The Advances in Global Leadership series, with its finger firmly on the pulse of this exciting field, is a must-read book for scholars and practitioners alike.